مساهمة الأنشطة اللاصفية في تحسين الأداء اللغوي لدى الطفل تطبيق على المسرح المدرسي السنة الخامسة ابتدائي – أنموذجا – - دقلة، سعدية, حمو، عبير (university of eloued جامعة الوادي, 2018)
الملخص: إن الأنشطة المدرسية الصفية واللّاصفّية هي الأداة التي تستخدمها المدرسة لتمكين المتعلمين من مزاولة الأنشطة التي يرغبونها، والغرض منها باعتبارها إحدى الوسائل الفعالة التي تتبعها المدرسة لتحقيق وظيفتها الاجتماعية التربوية هو تنمية وصقل خبرات المتعلمين وتدريبهم أثناء ممارستهم الأنشطة المتنوعة المشجعة على العادات والسلوك الاجتماعية، وكل ذلك يدخل في إطار تقويم الذي يطلبه المجتمع الذي يعشون فيه. وفكرة النشاط المدرسي وصوره التطبيقية قديمة قدم بدايات التعليم نفسه ويقول أحد الفلاسفة: "إن الطفل يتعلم من بقائه ساعة واحدة في العمل البدوي أكثر مما يتعلمه في يوم كامل في التعليم النظري". حيث إن المسرح المدرسي لون من ألوان النشاط الذي يؤديه المتعلمون في مدارسهم تحت إشراف معلميهم ويحتفظ بفلسفته وأهدافه خاصة لتتناسب مع طبيعته ووظيفته. وأبرز ما قيل عن المسرح المدرسي أنه متكامل يؤدي دورا رئيسا في عملية التربية والتعليم. Résumé : Les activités scolaires et parascolaires sont la fonction utilisée par l'école dans l'exercice de ses fonctions dans le domaine de l'éducation et de la formation professionnelle, etc. dans un calendrier fourni par la communauté dans laquelle elles vivent. L'idée de l'activité scolaire et de son image appliquée remonte au début de la même éducation: un des philosophes dit: "Un enfant apprend à passer plus d'une heure dans le travail bédouin qu'il ne l'apprend dans une journée théorique". Comme le théâtre scolaire souffre depuis longtemps dans l'éducation dans les écoles sous la supervision de leurs enseignants et de célébrer sa philosophie et ses objectifs, en particulier en fonction de sa nature et de sa fonction. Et a souligné ce qui a été dit à propos de la basse théâtre de l'école intégrée. Summary note: The classroom and extracurricular activities are the tool used by the school to enable learners to practice the activities they desire. Its purpose as one of the effective means of the school to achieve its social educational function is to develop and refine the experiences of the learners and train them in the practice of various activities that encourage social customs and behavior. Within the framework of a calendar requested by the community in which they live. The idea of school activity and its applied image is as early as the beginning of the same education. One of the philosophers says: "A child learns from spending more than one hour in Bedouin work than he learns in a theoretical day." The school theater is a color of the activity of the learners in their schools under the supervision of their teachers and maintains his philosophy and objectives especially to suit his nature and function. He highlighted what was said about the school theater that it plays an integral role in the education process.
Keywords: الأنشطة المدرسية اللاّصفية , المسرح المدرسي , التعبير الكتابي و الشفوي: Activités parascolaires, théâtre scolaire, expression écrite et orale; Extracurricular activities, school theater, written and oral expression